Dopamine Receptor D3 Expression Is Altered in CD4+ T-Cells From Parkinson's Disease Patients and Its Pharmacologic Inhibition Attenuates the Motor Impairment in a Mouse Model - Elgueta, Daniela; Contreras, Francisco; Prado, Carolina; Montoya, Andro; Ugalde, Valentina; Chovar, Ornella; Villagra, Roque; Henríquez, Claudio; Abellanas, Miguel A.; Aymerich, María S.; Franco, Rarael; Pacheco, Rodrigo (Frontiers in Immunology, 2019)
Neuroinflammation constitutes a fundamental process involved in Parkinson's disease (PD). Microglial cells play a central role in the outcome of neuroinflammation and consequent neurodegeneration of dopaminergic neurons in the substantia nigra. Current evidence indicates that CD4+ T-cells infiltrate the brain in PD, where they play a critical role determining the functional phenotype of microglia, thus regulating the progression of the disease. We previously demonstrated that mice bearing dopamine receptor D3 (DRD3)-deficient CD4+ T-cells are completely refractory to neuroinflammation and consequent neurodegeneration induced by the administration of 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP). In this study we aimed to determine whether DRD3-signalling is altered in peripheral blood CD4+ T-cells obtained from PD patients in comparison to healthy controls (HC). Furthermore, we evaluated the therapeutic potential of targeting DRD3 confined to CD4+ T-cells by inducing the pharmacologic antagonism or the transcriptional inhibition of DRD3-signalling in a mouse model of PD induced by the chronic administration of MPTP and probenecid (MPTPp). In vitro analyses performed in human cells showed that the frequency of peripheral blood Th1 and Th17 cells, two phenotypes favoured by DRD3-signalling, were significantly increased in PD patients. Moreover, naïve CD4+ T-cells obtained from PD patients displayed a significant higher Th1-biased differentiation in comparison with those naïve CD4+ T-cells obtained from HC. Nevertheless, DRD3 expression was selectively reduced in CD4+ T-cells obtained from PD patients. The results obtained from in vivo experiments performed in mice show that the transference of CD4+ T-cells treated ex vivo with the DRD3-selective antagonist PG01037 into MPTPp-mice resulted in a significant reduction of motor impairment, although without significant effect in neurodegeneration. Conversely, the transference of CD4+ T-cells transduced ex vivo with retroviral particles codifying for an shRNA for DRD3 into MPTPp-mice had no effects neither in motor impairment nor in neurodegeneration. Notably, the systemic antagonism of DRD3 significantly reduced both motor impairment and neurodegeneration in MPTPp mice. Our findings show a selective alteration of DRD3-signalling in CD4+ T-cells from PD patients and indicate that the selective DRD3-antagonism in this subset of lymphocytes exerts a therapeutic effect in parkinsonian animals dampening motor impairment.